Fenomeni di generazione: narrazioni, problemi, metodologie (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This issue addresses the concept of generation in the field of media.
Keywords: Italian cinema; Music for film; Youtube; home movies; generations